Lenin--a biography - Service, Robert, 1947- (Cambridge, MA : Harvard University Press, 2000)
"This biography stresses the importance of Lenin's supportive family and of its ethnic and cultural background. Service examines his education, upbringing, and the troubles of his early life to explain the emergence of a rebel whose devotion to destruction proved greater than his love for the 'proletariat' he supposedly served. We are enabled to see how his intellectual preoccupations and inner rage underwent volatile interaction and propelled his career from young Marxist activist to founder of the communist party and the Soviet state - and how he bequeathed to Russia a legacy of political oppression and social intimidation that has yet to be expunged"--from the cover
Includes bibliographical references and index.
Donation of Anatole Shub
Keywords: Lenin, Vladimir Ilʹich, -- 1870-1924.; Heads of state -- Soviet Union -- Biography; Revolutionaries -- Russia -- Biography; Russia -- Politics and government -- 1894-1917.; Soviet Union -- Politics and government -- 1917-1936.